Influence of copper solvent extractant on microbial community structure of acidophilic microorganisms - Chen, Bo-wei; Li, Wen-juan; Liu, Xing-yu; Zhou, Gui-ying; Wen, Jian-kang (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2010)
The influence of different concentrations of copper solvent extractant ZJ 988 on the growth and activity of acidophilic microorganisms was studied and the microbial community structures were compared by 16S rRNA gene clone library analysis. The total bacteria numbers are reduced when 0.5% (volume fraction) extractant is added. The proportions of Acidithiobacillus ferrooxidans and Acidiphilium organovorum are increased, whereas the proportion of Leptospirillum ferriphilum is reduced. When the concentration of extractant is elevated to 1%, growth of all bacteria is inhibited. Clone library results reveal that the dominant bacteria in the culture solution with/without the extractant are At. ferrooxidans , A. organovorum and L. ferriphilum . The sensitivity order of the three bacteria to the extractant from the most to the least is found to be L. ferriphilum > At. ferrooxidans > A. organovorum .